2014
DOI: 10.4269/ajtmh.13-0646
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Antimalarial Chemoprophylaxis Recommendations for Wounded United States Military Personnel Admitted to a Military Treatment Facility

Abstract: Abstract. Malaria chemoprophylaxis is used as a preventive measure in military personnel deployed to malariaendemic countries. However, limited information is available on compliance with chemoprophylaxis among trauma patients during hospitalization and after discharge. Therefore, we assessed antimalarial primary chemoprophylaxis and presumptive antirelapse therapy (primaquine) compliance among wounded United States military personnel after medical evacuation from Afghanistan (June 2009-August 2011) to Landstu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Figure 5B shows the tradeoff between the ivermectin-effect duration and the campaign coverage that achieve about the same population-wide effect in a nonseasonal setting. Although malaria prevalence can be greatly reduced by MDA with artemisinin combination therapy alone if coverage is very high (~90%), we predict that incorporating long-lasting ivermectin can achieve similar results at more modest and historically and operationally achievable levels of population-wide MDA coverage (13,(15)(16)(17)(18). With the inclusion of long-acting ivermectin, we have the added benefit that transmission from nontreated individuals is reduced because there are fewer mosquitoes to become infected, and any mosquitoes picking up infectious parasites from these untreated individuals are likely to take one or more blood meals from ivermectin-treated individuals, and thus die, before becoming infectious themselves.…”
Section: Sustained Ivermectin Could Potentiate Efficacy Of Artemisini...mentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 5B shows the tradeoff between the ivermectin-effect duration and the campaign coverage that achieve about the same population-wide effect in a nonseasonal setting. Although malaria prevalence can be greatly reduced by MDA with artemisinin combination therapy alone if coverage is very high (~90%), we predict that incorporating long-lasting ivermectin can achieve similar results at more modest and historically and operationally achievable levels of population-wide MDA coverage (13,(15)(16)(17)(18). With the inclusion of long-acting ivermectin, we have the added benefit that transmission from nontreated individuals is reduced because there are fewer mosquitoes to become infected, and any mosquitoes picking up infectious parasites from these untreated individuals are likely to take one or more blood meals from ivermectin-treated individuals, and thus die, before becoming infectious themselves.…”
Section: Sustained Ivermectin Could Potentiate Efficacy Of Artemisini...mentioning
confidence: 95%
“…The effectiveness of MDA depends on obtaining sufficient and prolonged drug blood levels in the vast majority of the population, which can be difficult in resource-constrained or remote locations, and increases the cost of the MDA approach (13,15). Nonadherence, a well-recognized barrier to effective care in the developed world, has also been shown to contribute to MDA failure in the developing world during repeat dosing regimens (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that compliance with primary antimalarial prophylaxis among deployed soldiers ranges from 38 to 61% (Brisson et al, 2012; Kotwal et al, 2005; Newton et al, 1994; Whitman et al, 2010). Moreover, 74% of military personnel wounded in Afghanistan and evacuated to Landstuhl Regional Medical Center (LRMC; Germany) were prescribed doxycycline by clinicians in order to comply with antimalarial prophylaxis guidelines (Rini et al, 2014). While prophylaxis is warranted when serving in malaria-endemic regions, there are unavoidable consequences of extensive use of doxycycline, including potential for increased tetracycline resistance among S. aureus .…”
Section: 0 Introductionmentioning
confidence: 99%
“…[9] However,the effectiveness of MDA depends on achieving high enough blood levels in the majority of people in the community.Lack of drug adherence has been acritical issue in the developing world. [10,11] To this end, we sought to develop as ingle-dose administration of ivermectin which can amplify MDAc ampaigns because of its toxicity to the Anopheles mosquito that transmits malaria. [12] Thec hallenge was to develop an oral system that might last for at least two weeks and deliver ivermectin over this duration.…”
mentioning
confidence: 99%